Impact of feeding volumes in the first 24 h of life on neonatal feeding intolerance - Kumar, Navin; Oredein, Igbagbosanmi; Al-Nahar, Mohammed; Harris, Nathalee; Sampath, Venkatesh (Frontiers in Pediatrics, 2023)
Objective This study investigates whether volumes of intake in the first 24 h of life (24 HOL), in relation to birth weight (BW) and gestational age (GA), impact neonatal feeding intolerance (FI). Methods This study employed a retrospective chart review of 6,650 infants born at ≥35 weeks. The volumes of each formula feed per kg BW in the first 24 HOL were assessed. FI was defined as evidenced by chart documentation of emesis, abdominal distension, abdominal x-ray, and/or switching to a sensitive formula. Results Overall, the maximum volume of formula intake per feed was inversely correlated with GA and was higher in infants with FI (β = −1.39, p < 0.001) compared with infants without FI (β = −1.28, p < 0.001). The odds of emesis in late preterm infants with first feeding of >8 ml/kg [adjusted odds ratio (AOR) = 2.5, 95% confidence interval (CI): 1.4–4.6] and formula switching in the exclusively formula-fed group with volumes >10.5 ml/kg [AOR = 2.2, 95% CI (1.8–2.6)] were high. In the breastfeeding group, the odds of FI increased by 2.8-, 4.6-, and 5.2-fold with 5–10, 10–15, and >15 ml/kg of supplementations, respectively. Conclusion A higher volume of intake in relation to BW often exceeds the physiological stomach capacity of newborns and is associated with early FI. Optimizing early feeding volumes based on infant BW and GA may decrease FI, which may be an issue of volume intolerance.